Evaluation of the risk of SARS-CoV-2 infection and hospitalization in vaccinated and previously infected subjects based on real world data - Rossi, Maicol Andrea; Cena, Tiziana; Binala, Jefferson; Alessi, Daniela; Scotti, Lorenza; Faggiano, Fabrizio (Scientific reports, 2023)
The objective of our study was to determine the joint protective effect of a previous SARS-CoV-2 infection and vaccination on the risk of a new infection and hospitalization. Two case–control studies nested in a cohort of COVID-19 patients cared for by the Local Health Unit (LHU) of Vercelli, Italy, were performed, one to estimate the risk of infection and the second to estimate the risk of hospitalization. Each new infection and hospitalization was matched with up to 4 disease-free subjects who were the same age, sex and index date (i.e., controls). Study subjects were followed up from cohort entry date to disease outcome, end of follow-up or emigration. Vaccination was associated with a 36% (OR 0.64; 95%CI 0.62–0.66) and 90% (OR 0.10; 95%CI 0.07–0.14) reduction in the risk of infection and hospitalization, respectively. Prior infection was associated with a 65% (OR 0.35; 95%CI 0.30–0.40) and 90% (OR 0.10; 95%CI 0.07–0.14) reduction in the risk of infection and hospitalization, respectively. Vaccinated and recovered subjects showed a 63% (OR 0.37; 95%CI 0.34–0.14) and 98% (OR 0.02; 95%CI 0–0.13) reduction in the risk of infection and hospitalization, respectively. Vaccination remains an essential public health tool for preventing severe forms of COVID-19. Our study shows that vaccination or previous infection has a strong protective effect against Sars-CoV-2 hospitalization. The protective role against infection appears to be present although with a lower efficacy rate than that presented in the RCTs.